PERANCANGAN UI/UX PADA APLIKASI LINGUALY MENGGUNAKAN MOBILE-FIRST DESIGN DENGAN METODE GOAL-DIRECTED DESIGN - Syam, Ridwan Dwiyanto; Rahman, Syaiful; Bahri, Syamsul (KHARISMA Tech, 2025)
This research aims to design an optimal user interface and user experience for language learning applications with the Mobile-First Design approach with the Goal-Directed Design method, which focuses on user goals. User needs analysis was conducted through questionnaires, surveys, and observations to develop usage scenarios. UI design focused on clarity, intuitive navigation, and simple layout, as well as visual appeal. At the UX stage, responsive design principles and user experience testing were applied to ensure that the app could be accessed properly on various devices. After the improvement of the Lingualy application, an evaluation using the System Usability Scale (SUS) resulted in an average score of 74.8, falling into the category of “Acceptable”, with a predicate of “C” and a rating of “Good”. This research concludes that user-centered UI/UX design makes language learning more effective and enjoyable, and enables proficiency without the limitations of time and place.